Interregional Disparity and Spatial Autocorrelation of Access to Water and Sanitation in Indonesia - Keisha Disa Putirama (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
This study investigates the interregional district-level inequalities and the spatial associations of household access to sustainable water and sanitation in Indonesia between 2004 and 2018. The findings show that although the gap of household access to water and sanitation declined over years, the disparities among districts in Indonesia kept persisting. Related to proliferation, the access in the districts that never separated is higher than in others. Furthermore, this study also confirms the presence of spatial cluster/outlier of accesses, although it remains very weak. The majority of districts with high access are clustered in the western part of Indonesia, especially in Java island. At the same time, in the mountainous areas of Papua island and some districts in Sumatera island where forest land has been degraded into plantation and mining areas have relatively low access for years. These left-behind districts need government attention and support in order to provide more equitable access to water and sanitation for the people.